Accuracy of photorespiration and mitochondrial respiration in the light fitted by CO2 response model for photosynthesis - Niu, Zhengwen; Ye, Zi-Wu-Yin; Huang, Qi; Peng, Chunju; Kang, Huajing (Frontiers in Plant Science, 2025)
IntroductionAtmospheric CO2 elevation significantly impacts plant carbon metabolism, yet accurate quantification of respiratory parameters—photorespiration rate (Rp) and mitochondrial respiration rate in the light (Rd)—under varying CO2 remains challenging. Current CO2-response models exhibit limitations in estimating these parameters, hindering predictions of crop responses under future climate scenarios.MethodsLow-oxygen treatments and gas exchange measurements, calculating CO2 recovery/inhibition ratio in of wheat (Triticum aestivum L.) and bean (Glycine max L.) were employed to elucidate the biological significance and interrelationships of Rp and Rd. Model-derived estimates of Rp and Rd were compared with measured values to assess the accuracy of three CO2-response models (biochemical, rectangular hyperbola, modified rectangular hyperbola). Furthermore, the effects of ambient CO2 concentration (0~1200 μmol·mol-1) on the measured Rp and Rd were quantified through polynomial regression.ResultsThe A/Ca model achieved superior fitting performance over the A/Ci model. However, significant disparities persisted between A/Ca-derived Rp/Rd estimates and measurements (p < 0.05). CO2 concentration exhibited dose-dependent regulation of respiratory fluxes: Rp-measured ranged from 4.923 ± 0.171 to 12.307 ± 1.033 μmol (CO2) m-2 s-1 (wheat) and 4.686 ± 0.274 to 11.673 ± 2.054 μmol (CO2) m-2 s⁻ ¹ (bean), while Rd-measured varied from 0.618 ± 0.131 to 3.021 ± 0.063 μmol (CO2) m-2 s-1 (wheat) and 0.492 ± 0.069 to 2.323 ± 0.312 μmol (CO2) m-2 s-1 (bean). Polynomial regression revealed strong non-linear correlations between CO2 concentrations and respiratory parameters (R² > 0.891, p < 0.05; except bean Rp-Ca: R² = 0.797). Species-specific CO2 thresholds governed peak Rp (600 μmol·mol-1 for wheat vs. 1,000 μmol·mol-1 for bean) and Rd (400 μmol·mol-1 for wheat vs. 200 μmol·mol-1 for bean).DiscussionThese findings expose critical limitations in current respiratory parameter quantification methods and challenge linear assumptions of CO2-respiration relationships. They establish a critical framework for refining photosynthetic models by incorporating CO2-responsive respiratory mechanisms. The identified non-linear regulatory patterns and model limitations provide actionable insights for advancing carbon metabolism theory and optimizing crop carbon assimilation strategies under rising atmospheric CO2, with implications for climate-resilient agricultural practices.